2018
DOI: 10.1111/rec.12898
|View full text |Cite
|
Sign up to set email alerts
|

Restore and Renew: a genomics‐era framework for species provenance delimitation

Abstract: Here we present "Restore and Renew," a replicable framework for gathering and interpreting evolutionary, ecological, and genomic data in support of restoration practices. In an era of rapid climatic change and continuous widespread clearing, revegetation projects need to focus on producing resilient and long-term self-sustaining populations. Restore and Renew expands current knowledge of genetic provenance via genome-scan data, environmental niche modeling (ENM), and site-specific climate information. The samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 51 publications
1
75
0
Order By: Relevance
“…A second important question is how we might exploit geographic variation in conservation efforts to promote adaptation through targeted gene flow [29,104]. Central to this question is the problem of identifying how strongly a species is adapting to different aspects of climate: for example, a species might show strong local adaptation to temperature but only moderate adaptation to precipitation.…”
Section: Discussionmentioning
confidence: 99%
“…A second important question is how we might exploit geographic variation in conservation efforts to promote adaptation through targeted gene flow [29,104]. Central to this question is the problem of identifying how strongly a species is adapting to different aspects of climate: for example, a species might show strong local adaptation to temperature but only moderate adaptation to precipitation.…”
Section: Discussionmentioning
confidence: 99%
“…To ensure empirical genetic data is utilized to facilitate informed provenance decisions, data on genetic diversity and structure and their links to environmental conditions should be made publicly available to stakeholders and non-experts including community groups and governments who often implement restoration programs. For example, the restore and renew website for terrestrial plants 2 (Rossetto et al, 2019) allows users to define a site to be restored, choose appropriate provenance within defined genetic populations and even provides provenance options to improve resilience (see "Revive -Restoring Extant or Historic Genetic Baselines"). No such platforms exist for marine systems but development of new marine restoration methods that will increase accessibility of 2 restore-and-renew.org.au marine restoration to diverse user groups and over large scales, will necessitate similar initiatives to ensure scientifically informed provenance decisions are made within the decade of restoration.…”
Section: Revive -Restoring Extant or Historic Genetic Baselinesmentioning
confidence: 99%
“…S12), which could be used to delineate seed sourcing strategies. In contrast to the commonly employed Generalized Dissimilarity Models (GDM) (Shryock et al, 2015;Gugger et al, 2018;Supple et al, 2018;Rossetto et al, 2019), our mapping approach based on sPCA allows incorporating GPA and predicting adaptive genetic variation from site-level data, which is particularly useful in areas lacking high-resolution environmental layers. Moreover, sPCA explicitly account for spatial autocorrelation in genetic composition, which is likely to play an important role explaining patterns of local adaptation (Lesica & Allendorf, 1999b;Richardson et al, 2014) (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of neutral genetic markers to identify independent demographic units is now common practice (Coates et al, 2018), few restoration studies have delineated seed sourcing strategies based on population genetic structure (Durka et al, 2017) or the genetic neighborhood size (the distance at which genetic composition stops being spatially autocorrelated) (Krauss & Koch, 2004;Krauss et al, 2013;Rossetto et al, 2019). On the other hand, only three restoration genomic studies so far have identified putative adaptive loci and then mapped adaptive genetic variation (Steane et al, 2014;Shryock et al, 2015;Martins et al, 2018).…”
Section: Introductionmentioning
confidence: 99%